2010
DOI: 10.1007/s11265-010-0450-4
|View full text |Cite
|
Sign up to set email alerts
|

Easy-hardware-implementation MMPF for Maneuvering Target Tracking: Algorithm and Architecture

Abstract: In this paper, we present an easy-hardwareimplementation multiple model particle filter (MMPF) for maneuvering target tracking. In the proposed filter, the sampling importance resampling (SIR) filter typically used for nonlinear and/or non-Gaussian application is extended to incorporating multiple models that are composed of a constant velocity (CV) model and a "current" statistical (CS) model, and the Independent Metropolis Hasting (IMH) sampler is utilized for the resampling unit in each model. Compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Figure 3 shows the IMH sampler architecture. When computing the acceptance probability, we use the modified method in [26] to avoid division computation. In particular, in our case, we accept particles following the procedure…”
Section: Processing Element Architecturementioning
confidence: 99%
“…Figure 3 shows the IMH sampler architecture. When computing the acceptance probability, we use the modified method in [26] to avoid division computation. In particular, in our case, we accept particles following the procedure…”
Section: Processing Element Architecturementioning
confidence: 99%
“…Because PF is based on the MC method, the computational complexity is inherently high and the real‐time processing may become an implementation difficulty. Fortunately, some recent researches have shown that with dedicated designed hardware circuits in field programable gate arrays platform, the processing rate can achieve an order of magnitude of 100 kHz . This indicates that the proposed communication system can meet the requirements in moderate data rate communications.…”
Section: Application To Secure Communicationmentioning
confidence: 93%
“…Target's location is predicted with division of the sum of all models estimations by the sum of particle weights which are obtained by resampling. Thus, A2 does not need model transition probabilities for determining the model and has a better processing time performance when compared to a traditional MMPF [17].…”
Section: Multi Model Particle Filtermentioning
confidence: 99%
“…The results of simulation given for 1000 particles showed that the error performance of the proposed PF is approximately similar to that of MMPF and it uses about 10% less time than MMPF. Hong et al proposed a MMPF structure consisting of a statistical model for maneuvering motion [17]. It is stated that, for the 0.01 noise level and 1000 particles, the presented algorithm has similar error to traditional MMPF and lower processing time at resampling step.…”
Section: Introductionmentioning
confidence: 99%